Financial Organization and Operations of the IMF (Revised 1998). (Pamphlet Series, 1998)
This paper discusses the financial organization and operations of the IMF. The policies and activities of the IMF are guided by its charter, known as the Articles of Agreement. The IMF is unique among intergovernmental organizations in its combination of regulatory, consultative, and financial functions, which derive from the purposes for which it was established. The IMF is concerned with not only the problems of individual countries but also the workings of the international monetary system as a whole. Its activities focus on promoting policies and strategies through which its members can work together to ensure a stable world financial system and sustainable economic growth.